The Governance-Innovation Nexus in MNEs: How HQ ‎ControlShapes Subsidiary Innovation and Performance - Cho , Moon Hwan; Park, Byung Il (International Journal of Accounting and Economics Studies, 2025)
This study examines how various dimensions of headquarters control—extent of control, focus of control, and formal mechanisms—affect ‎the innovation and financial performance of foreign subsidiaries. Based on agency theory and resource-based view (RBV), this study ‎empirically tests the conceptual model using survey data from 200 subsidiaries operating in China. The results of hierarchical regression ‎analysis show that control mechanisms have a positive effect on both incremental and radical innovation, and the effect on incremental ‎innovation is stronger. In contrast, the extent and focus of control did not have a significant effect on either type of innovation. Both types of ‎innovation displayed a significant positive relationship with financial performance, and the influence was particularly greater for radical ‎innovation. These results suggest that the control structure of headquarters needs to be aligned with the characteristics of innovation ‎activities. This study contributes to the international business literature by clarifying the specific roles of headquarters control and providing ‎practical implications for the balance between control and autonomy for managing global innovation‎.